Attitudes and beliefs of nursing students towards sexual health care - Ab Rashid, Nur Aida; Ahmad, Norfadzilah; Makhtar, Aniawanis (IIUM Press, 2022)
Introduction: Sexual health care refers to assessing sexual health, identifying the risks, and providing appropriate counselling related to sexuality. It is essential to have competency related to this care to prevent under-treated patient and further complications. This study aims to explore attitudes and beliefs among undergraduate nursing students at International Islamic University Malaysia (IIUM) Kuantan, Pahang toward sexual health care and its association with socio-demographic characteristics. Methods: A descriptive quantitative cross-sectional study with a convenience sampling was conducted among 239 students from March to May 2021. Data were gathered by using Google Forms questionnaires and distributed to all undergraduate nursing students through WhatsApp. The questionnaires were available in three parts: socio-demographic, students’ characteristics, and Sexual Attitude and Belief Survey (SABS). Data analysis was done by using SPSS version 20.0. Results: The majority of nursing students have moderate attitudes and beliefs in delivering sexual health care and Age group was significantly associated with SABS score (p<0.05). Conclusion: Although most nursing students have sufficient knowledge related to sexual health, they still feel uncomfortable and unable to diagnose patients with sexual problems.